2016
DOI: 10.1039/c6cp04775k
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the dissolution of polysulfides with cosolvent fluorinated diether towards high-performance lithium sulfur batteries

Abstract: The dissolution and shuttle of polysulfides in electrolytes cause severe anode corrosion, low coulombic efficiency, and a rapid fading of the capacity of lithium-sulfur batteries. Fluorinated diether (FDE) was selected as a cosolvent in traditional ether electrolytes to suppress the dissolution of polysulfides. The modified electrolytes lead to a negligible solubility of polysulfides, as well as decreased corrosion of the lithium anode. In an optimal system, the cells show improved cycling performance with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 39 publications
2
38
0
2
Order By: Relevance
“…Thet ypical design strategy involves adding fluorinated organic compounds such as fluorinated boronic esters, fluorinated ethers,f luorinated carbonates,a nd fluorinated alkylphosphates to the electrolyte. [79,[138][139][140][141][142] Of these,t he fluorinated boronic ester was found to be ad ual-functional additive,o ffering protection against over-charge as well as anion acceptor for lithium-ion batteries. [138] Zhang and coworkers reported that the use of fluorinated carbonate solvents contributed to the formation of ah igh-voltage electrolyte that produced fewer solid decomposition products on the surface of the anode (graphite,Li, or Li 4 Ti 5 O 12 )and the LiNi 0.5 Mn 1.5 O 4 cathode.T hese properties significantly improved the cycling stability at elevated temperatures.…”
Section: Electrolyte Design and Additivesmentioning
confidence: 99%
“…Thet ypical design strategy involves adding fluorinated organic compounds such as fluorinated boronic esters, fluorinated ethers,f luorinated carbonates,a nd fluorinated alkylphosphates to the electrolyte. [79,[138][139][140][141][142] Of these,t he fluorinated boronic ester was found to be ad ual-functional additive,o ffering protection against over-charge as well as anion acceptor for lithium-ion batteries. [138] Zhang and coworkers reported that the use of fluorinated carbonate solvents contributed to the formation of ah igh-voltage electrolyte that produced fewer solid decomposition products on the surface of the anode (graphite,Li, or Li 4 Ti 5 O 12 )and the LiNi 0.5 Mn 1.5 O 4 cathode.T hese properties significantly improved the cycling stability at elevated temperatures.…”
Section: Electrolyte Design and Additivesmentioning
confidence: 99%
“…Fluorinated ethers have also received attention for using in electrolytes due to their low viscosity, low melting point, high oxidation potential, low flammability, and the low solubility of polysulfides in fluorinated ethers. [38a] Fluorinated ethers such as 1,1,2,2‐tetrafluoro‐3‐(1,1,2,2‐tetrafluoroethoxy)propane,[38a] bis(2,2,2‐trifluoroethyl) ether, 1,1,2,2‐tetrafluoroethyl‐2,2,3,3‐tetrafluoropropyl ether,[38b,c,55] ethyl 1,1,2,2‐tetrafluoroethyl ether, 1,1,2,2‐tetrafluoroethyl‐2,2,2‐trifluoroethyl ether, and 1,3‐(1,1,2,2‐tetrafluoroethoxy)propane have been developed as co‐solvents to facilitate the formation of LiF‐rich layers on the anodes surface, suppressing the shuttle effect of polysulfides and improving the electrochemical performance of Li–S batteries.…”
Section: Interface Engineering For Anodesmentioning
confidence: 99%
“…Subsequently, the resultant PVIm[TFSI] was put into a pristine electrolyte solution (1 m LiTFSI in DOL/DME = 1/1 v/v, without polysulfides) for 24 h and the change in the UV–vis spectra of the electrolyte solution was monitored. The electrolyte solution containing the polysulfide‐trapped PVIm[TFSI] showed a characteristic absorption peak at ≈280 nm in contrast to the pristine electrolyte solution (Figure d), exhibiting the release of polysulfides from the PVIm[TFSI]. The abovementioned results demonstrated that the PVIm[TFSI] synthesized herein undergoes a diffusion‐driven anion exchange reaction with polysulfides, which is expected to enable the reversible trap/release of polysulfides during charge/discharge cycling in Li–S batteries.…”
Section: Resultsmentioning
confidence: 81%
“…As additional evidence to verify the polysulfide‐capturing capability of PVIm[TFSI], UV–vis absorption spectra of the polysulfide solution were examined as a function of PVIm[TFSI] concentration (Figure c). The intensity of the characteristic peak around wavelength of 280 nm, which is ascribed to S 6 2− and S 8 2− species, became weakened with the increase of PVIm[TFSI] concentration, which indicated a decrease in the polysulfide content in the solution.…”
Section: Resultsmentioning
confidence: 99%